Effects of adverse childhood events over metacognitions, rumination, depression and worry in healthy university students (Annals of Medical Research, 2021)
Aim: Adverse childhood experiences observed the various physical and mental problems that emerged in the later periods of life were found to be significantly associated. The aim of this study is to compare anxiety and depression, rumination and metacognitions of individuals who experienced adverse childhood events and individuals with no adverse childhood events, even though they do not develop any psychopathology.Material and Methods: The sample of the study consisted of 275 university students who were applied SCID-I and SCID-II and no psychopathology. Adverse Childhood Experiences Scale Turkish Form (ACE-TR), Metacognition Questionnaire-30 (MCQ-30), Ruminative Thought Style Questionnaire (RTSQ), Positive-Negative Beliefs about Rumination Scale, Penn State Worry Scale, Generalized Anxiety Disorder-7, Beck Depression Inventory were applied to volunteers who met the criteria of inclusion in the study. Results: Participant with ACE-TR score greater than 0, ‘Negative Beliefs about Uncontrollability and Danger’, ‘Lack of Cognitive Confidence’, ‘Need to Control Thoughts’, ‘Cognitive Self Consciousness’ and total scores were statistically higher than those with ACE-TR score 0. The participant with ACE-TR scores greater than 0 had RTSQ, PBRS, NBRS, NBRS -1, PSWQ, GAD-7 and BDI scores were statistically higher than those with ACE-TR score 0. Discussion: Even though negative childhood experiences do not lead to psychopathology, they may trigger the emergence of dysfunctional metacognitions which leads to more anxiety and rumination and make the individual vulnerable for further stressful life events and might decrease resilience.
Keywords: Metacogniton; adverse childhood events; rumination; worry; depression; anixety.